2012
DOI: 10.1242/jeb.079327
|View full text |Cite
|
Sign up to set email alerts
|

Sperm metabolism in pig: a role for peroxisome proliferator-activated receptor (PPAR)γ

Abstract: SUMMARYPeroxisome proliferator-activated receptor gamma (PPARγ) is a nuclear hormone receptor expressed predominantly in adipose tissue, also implicated in energy homeostasis. In this study, we used western blotting and immunofluorescence techniques to demonstrate for the first time that pig spermatozoa express PPARγ. To investigate the functional role of PPARγ in pig sperm, we evaluated its action on different events that characterize the biology of sperm cells, i.e. motility, capacitation, viability and acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…PPAR transcripts were significantly higher in high motile semen samples of rams [35]. Pig spermatozoa motility was increased by the PPAR-ɣ ligand PGJ2 and decreased by the specific GW9662 PPAR-ɣ antagonist [36]. Activation of PPAR-ɣ was required for spermatozoa motility in humans [37].…”
Section: Discussionmentioning
confidence: 99%
“…PPAR transcripts were significantly higher in high motile semen samples of rams [35]. Pig spermatozoa motility was increased by the PPAR-ɣ ligand PGJ2 and decreased by the specific GW9662 PPAR-ɣ antagonist [36]. Activation of PPAR-ɣ was required for spermatozoa motility in humans [37].…”
Section: Discussionmentioning
confidence: 99%
“…PG receptors have been described in Leydig cells (i.e., EP1, DP, FP, TP, and PPARg receptors; Walch et al 2003, Frungieri et al 2006, Schell et al 2007, Kowalewski et al 2009, Pandey et al 2009), Sertoli cells (e.g., EP1, EP2, EP3, EP4, DP, IP, FP, and PPARg receptors; Ishikawa & Morris 2006, Winnal et al 2007, Kristensen et al 2011, Matzkin et al 2012a, and the seminiferous tubule wall (PPARg receptors; Frungieri et al 2002a). DP prostanoid receptors have also been detected in germ cells of the fetal mouse testis (Moniot et al 2014), whereas functional PPARg and PGE receptors have been found in sperm (Schaefer et al 1998, Santoro et al 2013.…”
Section: Cox and Pgs In The Human Testismentioning
confidence: 99%
“…The effects of rosiglitazone can be mediated by the PPARγ receptor and or by the phosphorylation of the AMPK. In both cases Akt can be phosphorylated [23]. To test this hypothesis samples were pre-incubated in presence of Akt1/2 inhibitor (30μM), GW9662, inhibitor of PPARγ (10μM) and dorsomorphin, inhibitor of AMPK (100μM) and then incubated in presence of rosiglitazone 75μM.…”
Section: Resultsmentioning
confidence: 99%
“…The PPAR γ agonist rosiglitazone induced clear improvements in mitochondrial function, and reduced caspase 3 activity, these effects also linked to increased phosphorylation of Akt. Previous reports indicate the importance of Akt phosphorylation in sperm function [15, 16, 52, 53], and recently a link between PPARγ agonists and Akt phosphorylation in human [22] and pig spermatozoa [23] has been reported. Moreover strategies to maintain Akt phosphorylated in spermatozoa have proven to be successful in human sperm cryopreservation [52, 54]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation